The Muslim Bonaparte : Diplomacy and Orientalism in Ali Pasha's Greece. - Fleming, K. E. (Princeton modern Greek studies., 2014)
Ali Pasha of Ioannina (?1750-1822), the Ottoman-appointed governor of the northern mainland of Greece, was a towering figure in Ottoman, Greek, and European history. Based on an array of literatures, paintings, and musical scores, this is the first English-language critical biography about him in recent decades. K.E. Fleming shows that the British and French diplomatic experience of Ali was at odds with the ""orientalist"" literatures that he inspired. Dubbed by Byron the ""Muslim Bonaparte, "" Ali enjoyed a position of diplomatic strength in the eastern Adriatic; in his attempt to secede f